Observational study on the therapeutic management and economic burden of adult patients with moderate to severe plaque psoriasis in France – the POP study - A. P. Villani; N. Quiles Tsimaratos; A. Crochard; A. Gherardi; A. Panes; A. Schmidt; M. Hueber Kollen; I. Borget (Journal of Market Access & Health Policy)
ABSTRACTBackground: Data on the therapeutic management and healthcare cost of moderate to severe psoriasis in France are scarce.Objective: To assess the therapeutic management and economic burden of patients with moderate to severe psoriasis.Setting: This is a retrospective observational study on the Generalist Beneficiaries Sample of the National Health Data System.Patients and outcome measures:Adults with moderate to severe psoriasis (with a topical vitamin D derivative followed by systemic treatment or hospitalization for psoriasis) were included and followed-up from 1 January 2009 to 31 December 2018. Patients were matched to controls without psoriasis. Patients’ characteristics and healthcare cost from the National Health Insurance’s (NHI) perspective were described.Results: Overall, 1,848 and 5,544 adults were included in the psoriatic and control cohorts, respectively. The most frequent treatments were methotrexate (18.5% to 21.4% of patients by year), phototherapy (29.9% in 2010 down to 6.2% in 2018), and acitretin (25.9% in 2010 down to 8.6% in 2018). Overall, 19% of patients used biotherapies. The mean healthcare costs reimbursed by NHI was €5,365/psoriatic patient (including €2,685 potentially attributable to psoriasis), which was twice as high as in controls. In both cohorts, healthcare costs increased over time.Conclusion: Moderate to severe psoriasis healthcare costs are high. [Figure: see text]